Comparative efficacy of chemical peels and laser treatments in melasma: a meta-analysis of randomized controlled trials - Ingyu Lee; SeoWon Kang; JinHan Lee; Hyungin Cho; Ki Won Lee; Dongkeun Lim (Journal of Cosmetic Medicine)
Melasma is a chronic pigmentation disorder that is difficult to treat due to its recurrent nature. This meta-analysis evaluated the efficacy and safety of chemical peels and laser treatments in reducing pigmentation and associated risks like post-inflammatory hyperpigmentation (PIH). To compare chemical peels and laser treatments for melasma, focusing on their effectiveness in reducing pigmentation severity (Melasma Area and Severity Index) and assessing risks like PIH. We analyzed 15 randomized controlled trials comparing outcomes of chemical peels (e.g., glycolic acid, salicylic acid) and laser treatments (e.g., Q-switched Nd, fractional lasers). Outcomes included melasma severity reduction, PIH incidence, and patient satisfaction. Data were synthesized using standardized mean differences (SMD) with 95% confidence intervals (CI), and forest and funnel plots were used to evaluate efficacy and publication bias. Lasers showed higher efficacy in reducing melasma severity (SMD=0.82, 95% CI [0.60, 1.04], p<0.001) than chemical peels (SMD=0.65, 95% CI [0.45, 0.85], p=0.015). However, lasers had a higher risk of PIH, especially in darker skin types (Fitzpatrick IV-VI), while chemical peels were safer with fewer complications. Laser treatments effectively reduce melasma severity but increase PIH risk. Chemical peels, though slower, are safer for patients prone to adverse effects. Combination therapies and maintenance strategies may improve long-term outcomes in melasma